The Dhuha Prayer Habituation Strategy to Foster Children's Self-Confidence - Ummi Nur Latifah; Siti Marliah (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
Self-confidence is a fundamental aspect of early childhood social-emotional development, enabling children to communicate, interact, and participate actively in learning. However, some children still show low self-confidence, such as hesitating to speak in class, answering questions reluctantly, and depending on teacher assistance. This study aimed to describe the role of congregational Dhuha prayer in enhancing the self-confidence of children aged 5–6 years at ABA 2 Labuhan Kindergarten. A descriptive qualitative approach was employed involving 27 children in Group B. Data were collected through observations across five phases, interviews, and documentation, then analyzed using the Miles and Huberman interactive model. The findings showed that regular participation in congregational Dhuha prayer improved children's self-confidence. The number of children in the Very Well Developed (VWD) category increased from 10 to 15, while the Not Yet Developed (NYD) category declined from four children to none. Children became more confident in leading prayers, answering questions, speaking before their peers, and interacting with teachers and classmates. These findings suggest that congregational Dhuha prayer is an effective religious habituation strategy for strengthening young children's self-confidence and social-emotional development.